Manufacture and Faraday magneto-optical effect of highly transparent novel holmium aluminum garnet ceramics. (1st April 2021) - Wang, Mengyao; Lu, Bin
Abstract: A novel transparent magneto-optical holmium aluminum garnet (HoAG) ceramic with a high in-line transmittance of ~80.3 % at 589 nm (~97.0 % of the theoretical transmittance of HoAG single crystal) and a maximal infrared cut-off at ~6.5 μm was successfully fabricated by vacuum sintering at 1650 °C. The facile co-precipitation strategy was employed to yield the precipitation precursor with hollow structures upon calcination into the sphere-like HoAG particle with a narrow particle distribution. Silica sintering aid creates point defect of Ho 3+ vacancies to promote the HoAG densification rate during sintering by Si 4+ substitution for Al 3+ in tetrahedrally coordinated 24 ( d ) sites. The magneto-optical HoAG ceramic has Verdet constants of ~-154 rad/(T·m) at 635 nm and ~-36 rad/(T·m) at 1064 nm, which are higher than or similar to that of the commercial TGG single crystal. The thermal conductivity of the transparent HoAG ceramic was determined to be ~10.5 W/(m·K) at room temperature. Graphical abstract: Image, graphical abstract